PENGARUH PERISTIWA KENAIKAN HARGA BBM TAHUN 2022 TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY - Rindang Istikayani; Nurhazana (Politeknik Negeri Bengkalis, 2023)
Stock price movements are influenced by the development of environmental and macroeconomic activities. This is reflected in the market reaction. Market reaction can be measured by abnormal return and trading volume activity. This study aims to determine the effect of the fuel price increase on abnormal returns and trading volume activity before and after the event. This research is a type of quantitative research using the event study method. The research sample consisted of 44 companies incorporated in the LQ-45 index using a purposive sampling technique. The research period used is 20 exchange days with an estimated market adjusted model. This research used paired sample t-test and Wilcoxon signed rank test. The results of the AAR and ATVA tests showed a significance value greater than 0.05. The conclusion of the study is that there is no difference in abnormal returns and trading volume activity between before and after the 2022 fuel price hike. The relevance of event study research with companies in the scope of accounting involves an analysis of the impact of fuel price hike events that can affect company value, financial performance, and stock prices. Keywords: Event Study, Rise In Fuel Price, Abnormal Return, Trading Volume Activity, Accounting